2021
DOI: 10.3389/fnagi.2021.691710
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity Signatures of Apathy in Community-Living Older Adults

Abstract: Apathy predicts poor outcomes in older adults, and its underlying neural mechanism needs further investigation. We examined the association between symptoms of apathy and functional connectivity (FC) in older adults without stroke or dementia. Participants included 48 individuals (mean age = 70.90) living independently in the community, who underwent resting-state fMRI and completed the Apathy Evaluation Scale (AES). Seed-to-voxel analysis (cluster-level p-FDR <0.05, voxel threshold p < 0.001) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Therefore, damage to these tracts may play a role in affecting decision-making and response selection processes that may contribute to a significant reduction in self-initiated goal-directed actions consistent with a state of apathy, as suggested by the model proposed by Guimaraes et al [ 27 ]. This finding is consistent with previous observations reporting functional alterations in fronto-parietal networks [ 34 , 35 , 36 ] that have been interpreted as signs of enhanced cortical inhibition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, damage to these tracts may play a role in affecting decision-making and response selection processes that may contribute to a significant reduction in self-initiated goal-directed actions consistent with a state of apathy, as suggested by the model proposed by Guimaraes et al [ 27 ]. This finding is consistent with previous observations reporting functional alterations in fronto-parietal networks [ 34 , 35 , 36 ] that have been interpreted as signs of enhanced cortical inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Alterations observed in both the uncinate and inferior fronto-occipital fasciculi may also be consistent with a disruption to insular connections, since a previous study found a substantial overlap between these associative tracts and structural connections of three insular sub-regions [ 70 ]. The insula, in particular the left one, has been found to be more atrophic [ 32 ] and its functional connectivity with fronto-parietal circuits to be altered in apathetic patients with AD [ 35 ] and cognitively unimpaired older adults [ 36 ]. The insula is part of the salience network together with the ACC, an area considered to be particularly involved in motivation regulation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also showed that plasma NfL levels modulated patterns of FC between the insula and medial orbitofrontal cortex, two lightly myelinated cortical areas that appeared to be vulnerable to detrimental effects of aging (Bartzokis, 2011;Vidal-Piñeiro et al, 2016). Recent evidence has linked rs-FC patterns of insular cortex and orbitofrontal cortex to apathy (Jang et al, 2021), a multi-domain syndrome associated with poor outcomes and incident dementia in normal older adults (van Dalen et al, 2018), suggesting that impaired FC of these two regions may have unfavorable implications for aging. Tract tracing studies in primates have revealed that the anterior insula has prominent connections to the orbitofrontal cortex (Flynn et al, 1999), forming a functional unit that serves in the integration of complex autonomic, cognitive and emotional processes (Morel et al, 2013), all of them manifestly affected by aging (Salthouse, 2012).…”
Section: Plasma Nfl Levels Are Negatively Associated With Intracortic...mentioning
confidence: 62%
“…Six months after stroke, not only psychogenic apathy may be caused by psychological and social factors, but also organic secondary apathy may be caused by neurobiological changes 18 . The possible neural mechanism is the impairment of the brain network related to goal directed behavior (GDB) 19 , which includes the anterior Cingulate cortex (ACC) and the nucleus accumbens (NAcc) 8,20 . Another likely reason is that infarction may lead to functional disruption of the connective area after an acute stroke 21 .…”
Section: Introductionmentioning
confidence: 99%